Substituent effects on NMR spectroscopy of 2,2-dimethylchroman-4-one derivatives: Experimental and theoretical studies - Iguchi, Daniela (2020)
The attribution of 1H and 13C NMR signals of a library of 5-, 6- and 7-substituted 2,2-dimethylchroman-4-one derivatives is reported. Substituent effects were interpreted in terms of the Hammett equation, showing a good correlation for carbons para- to the substituent group, not for the meta- ones. Similarly, the Lynch correlation shows the additivity of the substituent chemical shifts in the case of both H and C nuclei, again with the exception of the carbons in the meta- position. Density Functional Theory (DFT)-predicted 1H and 13C chemical shifts correspond closely with experimentally observed values, with some exceptions for C NMR data; however, the correlation is valid only for the aromatic moiety and cannot be extended to the heterocyclic ring of the chroman-4-one scaffold.